Murder in the Shenandoah : making law sovereign in revolutionary Virginia / Jessica K. Lowe. - Lowe, Jessica K. (Studies in legal history., 2019)
On July 4, 1791, the fifteenth anniversary of American Independence, John Crane, a descendant of prominent Virginian families, killed his neighbor's harvest worker. Murder in the Shenandoah traces the story of this early murder case as it entangled powerful Virginians and addressed the question that everyone in the state was heatedly debating: what would it mean to have equality before the law - and a world where 'law is king'? By retelling the story of the case, called Commonwealth v. Crane, through the eyes of its witnesses, families, fighters, victims, judges, and juries, Jessica K. Lowe reveals how revolutionary debates about justice gripped the new nation, transforming ideas about law, punishment, and popular government.